Визначення картини поля обмоток високовольтного трансформатора напруги - Бржезицький, В.О.; Гаран, Я.О. (Електротехніка і електромеханіка, 2012)
A formula for determination of circular single-turn coil generated magnetic intensity at any point is derived to allow calculating magnetic field of transformers cylindrical windings.